2018
DOI: 10.1007/s00405-018-5130-1
|View full text |Cite
|
Sign up to set email alerts
|

Facial nerve dysfunction after superficial parotidectomy with or without continuous intraoperative electromyographic neuromonitoring: a prospective randomized pilot study

Abstract: In the present pilot study, the incidences of immediate and late facial nerve dysfunction were similar between patients with benign parotid tumors subjected to superficial parotidectomy with or without continuous intraoperative electromyographic neuromonitoring. However, immediate facial dysfunction was more severe among the non-monitored patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 37 publications
4
26
1
3
Order By: Relevance
“…Two prospective trials have found no benefit in reducing the incidence of postoperative facial weakness. 20 , 21 This is in line with our finding. Nevertheless, in the recent randomized trial carried out by Graciano et al, non-monitored patients had significantly more severe weakness.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Two prospective trials have found no benefit in reducing the incidence of postoperative facial weakness. 20 , 21 This is in line with our finding. Nevertheless, in the recent randomized trial carried out by Graciano et al, non-monitored patients had significantly more severe weakness.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, in the recent randomized trial carried out by Graciano et al, non-moni-tored patients had significantly more severe weakness. 21 Furthermore, a meta-analysis of 546 patients by Sood et al concluded that IFNM decreases the risk of temporary weakness but does not appear to influence the incidence of permanent facial nerve weakness. 22 In revision surgery, where the facial nerve is more difficult to identify and dissect due to scarring and fibrosis, the use of IFNM may be more useful.…”
Section: Discussionmentioning
confidence: 99%
“…Only seven (14%) patients in the current study developed temporary facial paralysis. This is in the lower range compared to rates previously demonstrated in the literature, where temporary facial paralysis following superficial parotidectomy has been found to range between 10 and 80% [4,22,23]. One possible explanation for this is that in most studies, a surgical drain was placed at the end of surgery.…”
Section: Discussionmentioning
confidence: 56%
“…Eine weitere von der Arbeitsgemeinschaft Speicheldrüsen-und Schilddrüsenerkrankungen unterstützte prospektive Studie an 100 Parotidektomien wies nach, dass Fazialismonitoring die Operationszeit in einer Ausbildungsklinik ohne Zunahme von Komplikation vermindert [101]. Eine Meta-Analyse hat darüber hinaus herausgearbeitet, dass das Fazialismonitoring bei Parotidektomie das Risiko zumindest von temporären Fazialisparesen verringert [102] Dies bestätigt auch noch einmal eine aktuelle randomisierte Studie ( ± Monitoring) [103]. Es wird dennoch sicher nicht flächendeckend in Deutschland mit Fazialismonitoring gearbeitet.…”
Section: Evidenz-basierte Daten Zum Fazialismanagementunclassified